Dual roles of anesthetics in postoperative cognitive dysfunction: Regulation of microglial activation through inflammatory signaling pathways - Zhang, Mengxue; Yin, Yiqing (Frontiers in Immunology, 2023)
Postoperative cognitive dysfunction (POCD) is a prevalent clinical entity following surgery and is characterized by declined neurocognitive function. Neuroinflammation mediated by microglia is the essential mechanism of POCD. Anesthetics are thought to be a major contributor to the development of POCD, as they promote microglial activation and induce neuroinflammation. However, this claim remains controversial. Anesthetics can exert both anti- and pro-inflammatory effects by modulating microglial activation, suggesting that anesthetics may play dual roles in the pathogenesis of POCD. Here, we review the mechanisms by which the commonly used anesthetics regulate microglial activation via inflammatory signaling pathways, showing both anti- and pro-inflammatory properties of anesthetics, and indicating how perioperative administration of anesthetics might either relieve or worsen POCD development. The potential for anesthetics to enhance cognitive performance based on their anti-inflammatory properties is further discussed, emphasizing that the beneficial effects of anesthetics vary depending on dose, exposure time, and patients’ characteristics. To minimize the incidence of POCD, we recommend considering these factors to select appropriate anesthetics.